2000
DOI: 10.2214/ajr.175.6.1751619
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of 100 Hepatic Metastases with a Mean Follow-Up of More Than 1 Year

Abstract: Radiofrequency ablation appears to be a promising therapeutic modality capable of extending the possibilities of partial hepatectomy and of efficiently treating small metastases percutaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
1
24

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(185 citation statements)
references
References 23 publications
7
153
1
24
Order By: Relevance
“…Distant recurrence (elsewhere in the liver or extrahepatic) rates vary from 28% to 84% [17,20]. Reported local recurrence rates (at the RFA site) range widely, from 2% to 60% [19,28,[31][32][33][34]. In our series 12% had local RFA site recurrence.…”
Section: Discussionmentioning
confidence: 66%
“…Distant recurrence (elsewhere in the liver or extrahepatic) rates vary from 28% to 84% [17,20]. Reported local recurrence rates (at the RFA site) range widely, from 2% to 60% [19,28,[31][32][33][34]. In our series 12% had local RFA site recurrence.…”
Section: Discussionmentioning
confidence: 66%
“…Local recurrence following open ablation varies between 6 % and 60 % and following percutaneous ablation between 10 % and 52 % (Table 3) [44,46,84,85]. All studies report lower rates of local recurrence in smaller tumours.…”
Section: Choice Of Approach Local Recurrencementioning
confidence: 99%
“…), thereby making comparisons with patients who have undergone complete surgical resection difficult. In general, studies with isolated RFA show a median survival duration of about 30 -35 months and a 3-year survival rate of 20%-36% [75,[82][83][84]. In a recent study comparing recurrence and outcome following hepatic resection, RFA, and combined resection and RFA for colorectal liver metastases, Abdalla et al [11] reported a significantly worse disease-free and overall survival rate for patients treated with RFA.…”
Section: Combined Local Therapy: Resection Plus Rfamentioning
confidence: 99%